Characterization of the O/ME‐SA/Ind‐2001d foot‐and‐mouth disease virus epidemic recorded in the Maghreb during 2014–2015. Issue 5 (22nd June 2022) - Pezzoni, G.; Calzolari, M.; Foglia, E. A.; Bregoli, A.; Nardo, A. Di; Sghaier, S.; Madani, H.; Chiapponi, C.; Grazioli, S.; Relmy, A.; Bakkali Kassimi, L.; Brocchi, E.
Abstract: The O/ME‐SA/Ind‐2001d has been the main foot‐and‐mouth disease virus (FMDV) lineage responsible for FMD epidemics outside the Indian subcontinent from 2013 to 2017. In 2014, outbreaks caused by this FMDV lineage were reported in Maghreb, where it was initially detected in Algeria and Tunisia and later in Morocco. This was the first incursion of an FMDV type O of exotic origin in the Maghreb region after 14 years of absence. In this study, we report analyses of both VP1 and whole‐genome sequences (WGSs) generated from 22 isolates collected in Algeria and Tunisia between 2014 and 2015. All the WGSs analysed showed a minimum pairwise identity of 98.9% at the nucleotide level and 99% at the amino acid level (FMDV coding region). All Tunisian sequences shared a single putative common ancestor closely related to FMDV strains circulating in Libya during 2013. Whereas sequences from Algeria suggest the country experienced two virus introductions. The first introduction is represented by strains circulating in 2014 which are closely related to those from Tunisia, the second one, of which the origin is more uncertain, includes strains collected in Algeria in 2015 that gave origin to the 2015 outbreak reported in Morocco. Overall, our results demonstrated that a unique introduction of O/Ind‐2001d FMDV occurred in Maghreb through Tunisia presumably in 2014, and from then the virus spread into Algeria and later into Morocco.